Ras, Kuasa, dan Kekerasan Kolonial di Hindia Belanda - Iqra Pandu Wijaya (Jurnal Sejarah Indonesia, 2025)
This article is a review of the book "Race, Power, and Colonial Violence in the Dutch East Indies, Period 1808-1830," written by Peter Carey and Farish A. Noor in 2022. This review article, in addition to discussing the book's content and ideas about colonialism in the Dutch East Indies, also reveals cases beyond warfare and violence, namely the racial concepts developed by European scholars that later fueled the colonialists' mistreatment of indigenous people. The purpose of this review article is to provide new insights into colonialism in the Dutch East Indies beyond the concepts of warfare and indigenous resistance.